2017
DOI: 10.1371/journal.pone.0189462
|View full text |Cite
|
Sign up to set email alerts
|

Age-related reduction of adaptive brain response during semantic integration is associated with gray matter reduction

Abstract: While aging is associated with increased knowledge, it is also associated with decreased semantic integration. To investigate brain activation changes during semantic integration, a sample of forty-eight 25–75 year-old adults read sentences with high cloze (HC) and low cloze (LC) probability while functional magnetic resonance imaging was conducted. Significant age-related reduction of cloze effect (LC vs. HC) was found in several regions, especially the left middle frontal gyrus (MFG) and right inferior front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…It seems, that areas naturally attributed to aging are also needing the least amount of EV energy to yield a significant result. Most interestingly areas responsible for motion control and motor processes, cognitive processing and decision making, memory encoding and retrieval, decision-making, emotions, language processing, inhibitory control and regulation of sleep as well as alertness (namely putamen, orbifrontal cortex, parahippocampal gyrus, amygdala, caudate nucleus and thalamus) are displaying the strongest correlations and are in line with other publications reporting aging effects in the brain (e.g., Brodoehl et al, 2013 ; Zhuang et al, 2017 ; Zhu et al, 2017 ). On the contrary, areas for processing visual information like calcarine, cuneus, angular gyrus among other occipital regions need almost all EV energy if they reach significance at all, hinting at an age independence, see Supplementary Table 3 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It seems, that areas naturally attributed to aging are also needing the least amount of EV energy to yield a significant result. Most interestingly areas responsible for motion control and motor processes, cognitive processing and decision making, memory encoding and retrieval, decision-making, emotions, language processing, inhibitory control and regulation of sleep as well as alertness (namely putamen, orbifrontal cortex, parahippocampal gyrus, amygdala, caudate nucleus and thalamus) are displaying the strongest correlations and are in line with other publications reporting aging effects in the brain (e.g., Brodoehl et al, 2013 ; Zhuang et al, 2017 ; Zhu et al, 2017 ). On the contrary, areas for processing visual information like calcarine, cuneus, angular gyrus among other occipital regions need almost all EV energy if they reach significance at all, hinting at an age independence, see Supplementary Table 3 .…”
Section: Discussionsupporting
confidence: 88%
“…Changes in brain organization due to healthy aging have been reported in several studies (e.g., Brodoehl et al, 2013 ; Beason-Held et al, 2016 ; Goldstone et al, 2016 ; La Corte et al, 2016 ; He et al, 2017 ; Peterson et al, 2017 ; Siman-Tov et al, 2017 ; Tremblay et al, 2017 ; Zhuang et al, 2017 ; Zhu et al, 2017 ). In accordance to Liu et al ( 2013 ), Toussaint et al ( 2014 ), and Sokunbi et al ( 2015 ) non-linear brain complexity measures, derived from information theory, find changes in brain complexity as a result of healthy aging as well.…”
Section: Introductionmentioning
confidence: 88%
“…Consistent with the amplitude change pattern, the N400 is sensitive to semantic congruency, and this sensitivity was declined in the older adults. Such a reduced semantic integration effect could be explained by reduced brain functional response or brain shrinkage as observed in previous studies (Diaz et al, 2016;Grossman et al, 2002;Peelle et al, 2010;Tremblay, Dick, & Small, 2013;Zhu et al, 2017), or inefficient information transmission across the language network (Diaz et al, 2016;Fedorenko & Thompson-Schill, 2014).…”
Section: Discussionmentioning
confidence: 65%
“…The reduced N400 effect in older adults has been linked to less efficiency in pre-activating semantic features of coming words ( Federmeier and Kutas, 2005 ; Federmeier et al, 2010 ; DeLong et al, 2012 ) and integrating the words into context ( Hagoort et al, 2004 ; Zhu et al, 2012 ). Similarly, fMRI studies of older adults have revealed under-recruitment in the left frontal-temporal regions in poorer readers compared to better readers ( Grossman et al, 2002b ) or in older adults compared to younger adults ( Zhu et al, 2017 ). The reduction of the N400 effect, however, was not correlated with accuracy differences between conditions in either group.…”
Section: Discussionmentioning
confidence: 98%